1997
DOI: 10.1038/38236
|View full text |Cite
|
Sign up to set email alerts
|

External supply of oxygen to the atmospheres of the giant planets

Abstract: The atmospheres of the giant planets are reducing, being mainly composed of hydrogen, helium and methane. But the rings and icy satellites that surround these planets, together with the flux of interplanetary dust, could act as important sources of oxygen, which would be delivered to the atmospheres mainly in the form of water ice or silicate dust. Here we report the detection, by infrared spectroscopy, of gaseous H2O in the upper atmospheres of Saturn, Uranus and Neptune. The implied H2O column densities are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
211
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(233 citation statements)
references
References 30 publications
21
211
1
Order By: Relevance
“…Recent modeling of the processes taking place in the solar nebula are compatible with the deuterium enrichment with respect to the protosolar D/H ratio either measured in LL3 meteorites and comets (Mousis et al 2002;Eberhardt et al 1995;Bockelée-Morvan et al 1998;Meier et al 1998) or estimated from solar system outer planets HD measurements (Feuchtgruber et al 1999), below the 10 −3 limit. These values are much lower than the dark cloud values for other species (≤a few 10 −2 ).…”
Section: A Possible Scenario For Deuterium Enrichment?mentioning
confidence: 66%
“…Recent modeling of the processes taking place in the solar nebula are compatible with the deuterium enrichment with respect to the protosolar D/H ratio either measured in LL3 meteorites and comets (Mousis et al 2002;Eberhardt et al 1995;Bockelée-Morvan et al 1998;Meier et al 1998) or estimated from solar system outer planets HD measurements (Feuchtgruber et al 1999), below the 10 −3 limit. These values are much lower than the dark cloud values for other species (≤a few 10 −2 ).…”
Section: A Possible Scenario For Deuterium Enrichment?mentioning
confidence: 66%
“…The similar H 2 O fluxes per unit area into the four giant planets and Titan (Feuchtgruber et al 1997;Coustenis et al 1998;Moses et al 2000), combined with the rather constant dust flux (∼3×10 −18 g cm −2 s −1 ) measured in interplanetary space beyond 5 AU (Landgraf et al 2002) have been regarded as evidence that micrometeoroids -interplanetary (IDPs) or interstellar -are the dominant source (Moses et al 2000). Along with the evidence that the H 2 O present in Jupiter's atmosphere results from the Shoemaker-Levy 9 1994 impact -and that CO in Jupiter, Saturn, and Neptune Cavalié et al 2010;Lellouch et al 2005) also result from ancient cometary impacts -our inference that Enceladus is a quantitatively viable source of Saturn's water clearly shifts the paradigm towards local or sporadic sources playing a more important role.…”
Section: Discussion and Implications For The Source Of Water In Saturmentioning
confidence: 99%
“…Emission lines due to water vapor in the far-infrared spectrum (λ > 30 μm) of the giant planets and Titan, first discovered by ISO (Feuchtgruber et al 1997;Coustenis et al 1998) prove the existence of an external supply of water to these reducing atmospheres. At Saturn and Jupiter, spectrally resolved observations of the fundamental 1 10 -1 01 line of ortho-H 2 O at 557 GHz (538 μm), obtained by SWAS in September 1999 (Bergin et al 2000), indicated a ∼10% contrast emission with ∼20 km s −1 width.…”
Section: Observations and Initial Interpretationmentioning
confidence: 99%
“…On the other hand, space-based observatories such as ISO (Kessler et al 1996) and Herschel (Pilbratt et al 2010) have access to the mid-to far-infrared rotational (R-branch) lines of HD (Ulivi et al 1991, see also Table 2). While the Voyager/IRIS instrument could not detect these lines because of its insufficient spectral resolution, observations by the medium-to-high resolution spectrometers ISO-SWS (de Graauw et al 1996) and ISO-LWS (Clegg et al 1996) resulted in D/H values with significantly improved precision for all four giant planets (Griffin et al 1996;Encrenaz et al 1996;Feuchtgruber et al 1999;Lellouch et al 2001). The baseline spectral response calibration of the ISO-LWS instrument was obtained from Uranus observations.…”
Section: Introductionmentioning
confidence: 99%